1981
DOI: 10.2307/3897859
|View full text |Cite
|
Sign up to set email alerts
|

Early Succession in Aspen Communities following Fire in Western Wyoming

Abstract: Aspen clones in varying degrees of deterioration were burned in northwestern Wyoming in an attempt to regenerate the site. Large numbers of aspen suckers are necessary to perpetuate these stands under current heavy ungulate use. Sucker numbers doubled the second year after burning and by the end of the third year bad returned to near preburn levels of 15,000~20,000 suckers per bectare. This slight increase in sucker numbers is probably not sufficient to regenerate the stands under current browsing pressures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 4 publications
2
63
1
Order By: Relevance
“…During the first 5 to 10 years following stand-replacing fire, grass and forb biomass generally increases. Grass and forb biomass decreased the first growing season after fire in aspen stands in Wyoming but increased the second and third growing seasons to above preburn levels (Bartos and Mueggler 1981). On "heavily burned" sites, grass recovered more slowly than forbs.…”
Section: Western Forests ________________ Rocky Mountain Forestmentioning
confidence: 93%
“…During the first 5 to 10 years following stand-replacing fire, grass and forb biomass generally increases. Grass and forb biomass decreased the first growing season after fire in aspen stands in Wyoming but increased the second and third growing seasons to above preburn levels (Bartos and Mueggler 1981). On "heavily burned" sites, grass recovered more slowly than forbs.…”
Section: Western Forests ________________ Rocky Mountain Forestmentioning
confidence: 93%
“…Burning or clear-cutting aspen stands has been reported to increase aspen suckering from 17 000 to 150 000 stems/ha (Patton and Avant 1970;Bartos 1979;Bartos and Mueggler 1981;Bartos and Mueggler 1982;Crouch 1983). These values are 1.5 to 30 times greater than stem densities reported for the FALL treatment.…”
Section: Juniper Removal and Aspen Responsementioning
confidence: 99%
“…Bartos and Mueggler (1981) reported that herbaceous production peaked in the second and third year after a high-severity fire in aspen stands in northwestern Wyoming. Herbaceous cover in the FALL treatment did not reach full potential, and a sizeable area of bare ground remained open to further colonization (Fig.…”
Section: Ground Cover Dynamicsmentioning
confidence: 99%
“…Horton and Hopkins (1965) found it impossible to prevent root sprouting by intense burning. Brown (1985), while not relating specifically to the seral age of aspen stands, suggested the following results (based on work by Bartos and Mueggler (1981) and Horton and Hopkins (1965)) would likely occur under three levels of fire severity:…”
Section: Montane Conifer Forest (Mixed Conifer Series) Rocky Mountainmentioning
confidence: 99%